Historic case studies reflecting sources of change in the theory of musical scales and modes in the West - Smith, David (College of Music, 2024)
This thesis seeks to co-ordinate two approaches to the study of scale and mode theories in the Western tradition. First, through a selection of eleven casestudies, it isolates instances of significant change in that theory. The selection, ranging from ancient Greek to contemporary theories, is intended not only to cover a broad chronological sampling, but also to demonstrate different sorts of change-change as conscious synthesis of available materials, change as intensification, change as repristination, change as personal innovation. Second, each case-study attempts to locate the theory dealt with ( and the changes observed) within the context of broader currents of contemporaneous thought; to show the mutual influences operating between musical thought and other fields; and to suggest thereby the function and meaning of these divisions of tonal space in wider climates of thought and feeling. Thus, the three chapters devoted to ancient Greek theory (1-3) place the various theorists dealt with against a background of expanding Greek mathematics, in particular the shift from arithmetical to geometrical approaches. The links with Greek religion and philosophy are also sifted, in a search for the likeliest determinants of theory. Additionally, though this is largely an "ideal" tradition, the relations between theory and practice are discussed. Two chapters ( 4-5) deal with scale/mode theory in the early middle ages. In line with the more optimistic understandings of pre-1200 culture, the first argues for a demonstrable synthesis of theoretical ideas-closely conditioned by both liturgical practice and educational goals-in the most important Carolingian treatises, a synthesis that provided the framework for much later theorizing, both in content and style. The second chapter-chiefly by means of a collection of texts (with translations)-investigates the centrality of musico-theoretical terminology in early medieval discourse, especially the question of musical "affects". Two chapters (6-7) are devoted to Renaissance themes. The first, in juxtaposing the figures of Franchino Gafori and Johannes Kepler, highlights two areas common to them: cosmic conceptions of music and the "doctrine" of proportions. The conclusions drawn are (i) that these otherwise distant figures stand !ogether in the tradition of the "rational artist"; (ii) that their association in this chapter may stand as a symbol of the intimate relations between art and science in this period (approximately 1480-1620). Chapter 7 considers the High Renaissance revival of modal theory against the background of the series of eruptions that commonly go by the names "Reformation" and "Counter-Reformation". It is argued there that the 8- and 12- mode schemes were appropriated by a tradition (traced back to the early 1400s) of musical works being used ·as "emblems" of political, social or religious affiliation. The after-life of the modal schemes-they were a spent force in music by c.1630-is traced in other art forms. Finally, four chapters (8-11) are devoted to the creative theorizing, both explicit and occult, of four modern composers-Debussy, Messiaen, Bart6k and Xenakis. All four offer much material in the area of scale/mode innovation. The chapter on Debussy concentrates on his use of the whole-tone scale, in particular the evidences of its systematic application and the possibility of its functioning as a musical symbol. Messiaen has installed "mode" as a central category in his musical thought. The lengthy case-study devoted to him endeavours to highlight both the expansion of the idea in the course of his career and the preservation of certain of its aspects through his various stylistic renewals. The definition of mode also involves a consideration of parametric analogies in his thought. Bart6k's polymodal chromaticism is a widely-used analytical tool, but its relation to his unusual habits of notation has been largely ignored. By focussing on this problem, details omitted by Bart6k from the general explanations of his chromatic technique can be fixed. Xenakis's idea of "sieving" brings the thesis up to the present. In detailing his approach to the formalization of scale structures, his links with-and precedents in-modernist thought are clarified.